2016
DOI: 10.3389/fnhum.2016.00563
|View full text |Cite
|
Sign up to set email alerts
|

Effective Connectivity within the Mesocorticolimbic System during Resting-State in Cocaine Users

Abstract: Objective: Although effective connectivity between brain regions has been examined in cocaine users during tasks, no effective connectivity study has been conducted on cocaine users during resting-state. In the present functional magnetic resonance imaging study, we examined effective connectivity in resting-brain, between the brain regions within the mesocorticolimbic dopamine system, implicated in reward and motivated behavior, while the chronic cocaine users and controls took part in a resting-state scan by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…We employed stochastic DCM, which allows for modelling of random neuronal noise in 559 the system, to improve network resolution in brainstem areas significantly affected by physiological 560 noise (Brooks et al, 2013). This routine was shown to improve the characterization of network 561 structure and parameter inference over deterministic DCM (Daunizeau et al, 2012;Osório et al, 562 2015) and has been widely used in resting state and task-based fMRI studies since its release (Kahan 563 et al, 2014;Ma et al, 2015Ma et al, , 2014Ray et al, 2016;Zhang et al, 2015). Bayesian Model selection 564 validated the results of the gPPI by excluding, for lack of evidence, a model where no connection was 565 modulated by task.…”
Section: Regions Whose Activity Correlates With Analgesic Effectmentioning
confidence: 99%
“…We employed stochastic DCM, which allows for modelling of random neuronal noise in 559 the system, to improve network resolution in brainstem areas significantly affected by physiological 560 noise (Brooks et al, 2013). This routine was shown to improve the characterization of network 561 structure and parameter inference over deterministic DCM (Daunizeau et al, 2012;Osório et al, 562 2015) and has been widely used in resting state and task-based fMRI studies since its release (Kahan 563 et al, 2014;Ma et al, 2015Ma et al, , 2014Ray et al, 2016;Zhang et al, 2015). Bayesian Model selection 564 validated the results of the gPPI by excluding, for lack of evidence, a model where no connection was 565 modulated by task.…”
Section: Regions Whose Activity Correlates With Analgesic Effectmentioning
confidence: 99%
“…The contribution of reduced VTA activity to mesolimbic affective disorders is supported by the finding that deep brain stimulation (DBS) of the VTA or the associated medial forebrain bundle is effective in treating chronic refractory cluster headaches and treatment-resistant depression (36,37). Alterations in VTA-NAc connectivity have also been observed in individuals with substance abuse disorders during active use as well as during abstinence phases; such changes may further affect executive or affective pain-processing centers (25,38,39). Specifically, changes in VTA-NAc connectivity in individuals with substance abuse disorders occur in an opposite direction to those observed in individuals with depression, with 3-day abstinent cocaine users showing increased effective connectivity from the VTA to the NAc and medial PFC (mPFC) (38).…”
mentioning
confidence: 99%
“…Alterations in VTA-NAc connectivity have also been observed in individuals with substance abuse disorders during active use as well as during abstinence phases; such changes may further affect executive or affective pain-processing centers (25,38,39). Specifically, changes in VTA-NAc connectivity in individuals with substance abuse disorders occur in an opposite direction to those observed in individuals with depression, with 3-day abstinent cocaine users showing increased effective connectivity from the VTA to the NAc and medial PFC (mPFC) (38). However, another study found decreased functional connectivity between the VTA and NAc of active cocaine users (39).…”
mentioning
confidence: 99%
“…The purpose of the present research was to investigate EC among all the MCLS brain areas [ 2 ] in cocaine smokers at resting-state using fMRI. This research is an extension of Gu et al [ 9 ] and Ray et al [ 8 ], and provides the first comprehensive examination of EC within cocaine users’ MCLS, utilizing baseline BOLD signal. The spatial patterns of resting-state correlation data are stable, in that they are similar across multiple resting-states (such as eyes-open and fixation) and across individuals and sessions.…”
Section: Introductionmentioning
confidence: 92%
“…Using functional magnetic resonance imaging (fMRI) technique, resting-state functional connectivity (RSFC; how individual brain regions are integrated during resting-state) has been examined on MCLS in cocaine users [ 8 ]. Also, a few effective connectivity (EC; the causal influence that one brain region exerts over another) studies have been conducted on cocaine users during resting-state scans and experimental tasks (working memory, response inhibition) [ 8 ]. The purpose of the present research was to investigate EC among all the MCLS brain areas [ 2 ] in cocaine smokers at resting-state using fMRI.…”
Section: Introductionmentioning
confidence: 99%